Insights into the electronic structure of OsO2 using soft and hard x-ray photoelectron spectroscopy in combination with density functional theory - Regoutz,A; Ganose,AM; Blumenthal,L; Schlueter,C; Lee,T-L; Kieslich,G; Cheetham,AK; Kerherve,G; Huang,Y-S; Chen,R-S; Vinai,G; Pincelli,T; et al. (Physical Review Materials, 2019)
Theory and experiment are combined to gain an understanding of the electronic properties of OsO2, a poorly studied metallic oxide that crystallizes in the rutile structure. Hard and soft valence-band x-ray photoemission spectra of OsO2 single crystals are in broad agreement with the results of density-functional-theory calculations, aside from a feature shifted to high binding energy of the conduction band. The energy shift corresponds to the conduction electron plasmon energy measured by reflection electron energy loss spectroscopy. The plasmon satellite is reproduced by many-body perturbation theory.